2016
DOI: 10.5005/jp-journals-10005-1345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antibacterial Efficacy of Type II Glass Ionomer Cement, Type IX Glass Ionomer Cement, and AMALGOMER™ Ceramic Reinforcement by Modified “Direct Contact Test”: An in vitro Study

Abstract: Background: Streptococcus mutans (ATCC25175) has a profound effect on the incidence of dental decay in the human population. Many studies have been performed to assess the antimicrobial activity of different cements. However, little or no information is available about the antibacterial properties of Type II glass ionomer cement (GIC), Type IX GIC, and AMALGOMER™ ceramic reinforcement (CR).Aim: To comparatively evaluate the antibacterial activity of Type II GIC, Type IX GIC, and AMALGOMER™ CR by modified direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Unlike other studies, in the current study, the material groups showed similar bacterial adherence . Hugar et al evaluated the bacterial density on Amagomer CR, Type II GIC and Type IX GIC without using saliva. Amalgomer CR showed better antibacterial effects compared with Type II GIC and Type IX GIC.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies, in the current study, the material groups showed similar bacterial adherence . Hugar et al evaluated the bacterial density on Amagomer CR, Type II GIC and Type IX GIC without using saliva. Amalgomer CR showed better antibacterial effects compared with Type II GIC and Type IX GIC.…”
Section: Discussionmentioning
confidence: 99%
“…This results were in accordance with Sultan (2019) (23) who found that Amalgomer showed statistically significant the lowest value for the mean diameter of inhibition zone after 48 hours. However, this finding was in disagreement with Hugar et al (2016) (24) who demonstrated that Amalgomer have high antibacterial effect. This may attribute to the different incubation periods as the antibacterial effect were taken after 1 hour, 1st, 3rd, 5th, and 7th day.…”
Section: Discussionmentioning
confidence: 53%
“…It was carefully avoided that the substance would run to the bottom of the well since that would obstruct the light's route through the microplate well and result in erroneous readings. Optical density measurements were read every hour for 6, 24, 48 and 72 hours in each well (An ELISA Reader Thermo Labsystems Multiskan, China) at 630 nm (Hugar et al 2016;Kurt et al 2021).…”
Section: Direct Contact Test For Antibacterial Activitymentioning
confidence: 99%